Dynamic bifurcation for a three-species cooperating model - Li, Junyan; Wu, Ruili (Journal of physics. Conference series, 2021)
A dynamic bifurcation analysis on a three-species cooperating model was presented and it was proved that the problem bifurcated an attractor as the parameter λ crossed the critical value λ 0 . The analysis was based on the attractor bifurcation theory together with the central manifold reduction.